Analysis of the Determinants of the Quality of Human Resources Project Management in Improving the Performance of Multi-Project Construction Time - Novaria, Rinaldy; Isradi, Muhammad (Jurnal Locus Penelitian dan Pengabdian, 2026)
Delays in construction project completion remain a major issue, particularly in multi-construction project environments characterized by limited resources and allocation conflicts. These conditions require high-quality project management human resources (HR) to ensure optimal project time performance. This study aims to analyze the effect of project management HR quality on time performance in multi-construction projects by examining five key dimensions: competence, loyalty, discipline, and integrity, with work motivation as a mediating variable. This study adopts a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 4 software. Data were collected through questionnaire surveys involving respondents engaged in three construction projects managed simultaneously. In addition, Importance Performance Analysis (IPA) was applied to identify practical priority indicators for improvement. The results indicate that the research model demonstrates very strong predictive capability, with coefficients of determination (R²) of 0.933 for time performance and 0.874 for work motivation. All HR quality variables have a positive and significant effect on project time performance, with the dominant influence order being discipline, competence, work motivation, loyalty, and integrity. Work motivation is proven to act as a mediating variable that strengthens the influence of HR quality on time performance. The IPA results identify four priority improvement indicators: technical competence, discipline in standard operating procedures and working hours, accuracy in project time control, and social motivation along with work environment support. This study concludes that improving the quality of project management HR implementation—particularly in the aspects of discipline and competence supported by work motivation—is a key factor in achieving effective time performance control in multi-construction projects.